(untitled) (LEARNing Landscapes, 2009)
We inquired into stories we lived whilst members of an ESL group. We used a narrative inquiry methodology. Our inquiry revealed tensions between identities given and identities continually negotiated between teacher, student and group member. Dewey’s (1938) concept of experience, notions of literacy acquisition (Collins & Blot, 2003; Cummins, 2001; Heath, 1983; Rose, 1989; Street, 1995), and Connelly and Clandinin’s (1990) ideas about teacher knowing, teacher identity and curriculum serve as the theoretical framework. Our inquiry helped us imagine educational landscapes which are responsive to ESL learners and a place where members of dominant discourse communities can wonder about the existence of hegemony.